Income and Wealth in the Irish Longitudinal Study on Ageing - Vincent O'Sullivan; Brian Nolan; Alan Barrett (Institute for the Study of Labor (IZA), 2013)
Between 2009 and 2011, data were collected under the first wave of The Irish Longitudinal Study on Ageing (TILDA). Over 8,500 people aged 50 and over and living in Ireland were interviewed on a wide range of topics covering socioeconomic and health issues. Our primary goals in this paper are (a) to present details on two of the variables which will be of particular interest to economists, namely income and wealth and (b) to discuss issues in relation to their use, in particular with respect to missing data. We describe how the income and wealth data were collected. We assess the quality of the income data by comparing them to those obtained through the European Union Statistics on Income and Living Conditions (EU-SILC). We find that the distribution of income in the TILDA sample resembles closely that found in a comparable sample from the EU-SILC. We undertake two pieces of analysis, by way of demonstrating potential applications of the data. First, we examine the joint distribution of income and assets and find that there is a small but non-negligible number of people who have low levels of income but high levels of assets and another similarly sized group in the opposite situation. Second, we consider the relationship between income/wealth and life satisfaction, another variable captured in TILDA. We find that income and housing wealth both affect life satisfaction but that the influence of income is much larger.
Keywords: D31; J14; 330; income; wealth; ageing